2006
DOI: 10.1093/icb/icj043
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection favors harmful mating in hermaphrodites more than in gonochorists

Abstract: Synopsis Hermaphroditic animals often exhibit mating mechanisms that seem more damaging than those in species with separate sexes. Our analyses indicate that this difference is real. While females only remate when the benefit is positive, hermaphrodites remate even when this implies losing female fitness. This occurs because hermaphrodites can outweigh losses in the female function by gaining paternity. In an extended model we ask whether this favors the evolution of more male harm in hermaphrodites. When male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 31 publications
2
48
1
Order By: Relevance
“…In such species, it could pay to increase investment in fertilization attempts, even if this results in lowered egg production. Choosing to invest in sexual conflict arms races over fecundity should be widespread among simultaneous hermaphrodites, according to recent theoretical work [36,37]. There is also empirical evidence suggesting that elevated mating rates may have opposite fitness effects via male and female sex functions [38,39].…”
Section: Intra-locus Sexual Conflict In Hermaphroditesmentioning
confidence: 99%
“…In such species, it could pay to increase investment in fertilization attempts, even if this results in lowered egg production. Choosing to invest in sexual conflict arms races over fecundity should be widespread among simultaneous hermaphrodites, according to recent theoretical work [36,37]. There is also empirical evidence suggesting that elevated mating rates may have opposite fitness effects via male and female sex functions [38,39].…”
Section: Intra-locus Sexual Conflict In Hermaphroditesmentioning
confidence: 99%
“…In the last few decades, there has been increasing attention on sexual selection in such hermaphroditic organisms (reviewed in Anthes, 2010;Leonard, 2013;Nakadera and Koene, 2013). Theoretical studies have suggested that the influences of sexual selection are significant in simultaneous hermaphrodites, as they are in species with separate sexes (Charnov, 1979;Michiels and Koene, 2006). Also, various conspicuous reproductive behaviours have been reported in hermaphroditic animals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First, theoretical analyses suggest that matings in simultaneous hermaphrodites may often be more harmful to the female function than expected for separate-sexed animals (Michiels and Koene 2006). This is because in contrast to females, simultaneous hermaphrodites should remate even if mating entails severe fitness costs for the female function, as long as they can compensate these costs by a sufficiently high male fitness benefit (Michiels and Koene 2006).…”
Section: Introductionmentioning
confidence: 99%
“…First, theoretical analyses suggest that matings in simultaneous hermaphrodites may often be more harmful to the female function than expected for separate-sexed animals (Michiels and Koene 2006). This is because in contrast to females, simultaneous hermaphrodites should remate even if mating entails severe fitness costs for the female function, as long as they can compensate these costs by a sufficiently high male fitness benefit (Michiels and Koene 2006). Second, in many simultaneously hermaphroditic species mating occurs reciprocally (i.e., each partner both donates and receives sperm during each mating), which inevitably links the mating strategies of both sex functions (Michiels 1998).…”
Section: Introductionmentioning
confidence: 99%